MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA MEDIK ANTARA DOKTER DAN PASIEN DALAM PERJANJIAN TERAPEUTIK - Ariep Mulyadi (2021)
Abstract The therapeutic transaction agreement is an agreement between a doctor and a patient which is a legal relationship. Therefore, it gives birth to rights and obligations between doctors and patients which have the potential to cause medical disputes between doctors and patients (malpractice). There are two ways to process medical dispute resolution, namely litigation (through court) and non-litigation (outside court). The litigation process is costly and time-consuming, and often results in one party being the winner and the other party being the loser. The protracted process in court causes a lot of sharp criticism of the judiciary when carrying out its functions, therefore it is necessary to improve the judicial system towards being effective and efficient, especially in medical disputes between doctors and patients. So the medical dispute mediation route between doctors and patients can be an alternative dispute resolution (ADR) that is more effective and efficient. The purpose of this study was to analyze the elements of a therapeutic agreement based on contract law in the Civil Code. And Analyzing mediation as an alternative to dispute resolution of therapeutic agreements for doctors and patients. To achieve this objective, research was conducted using normative juridical legal research methods. So this research approach uses the Statute Approach or research approach to legal products, by examining all laws and regulations related to what will be researched. Keywords: Therapeutic Agreement, Medical Dispute, Mediation